Белорус, Қазақстан жəне Ресей заңнамасының гармонизациялау (Journal of actual problems of jurisprudence, 2019)
Creation of the EuroAsian Union is caused by Belarus, Kazakhstan and Russia in aspiration of providingeconomic, military and other types of state, protecting common national interests which are caused byrequirement of strengthening social security of called countries population. In turn, social modernizationindissolubly contacts harmonization of all block of the social legislation, including labor and socially –security legislations in EAU territory.Authors made attempt to analyse separate aspects of three abovenamedstates labor legislation, to offer ways of their harmonization taking into account transformation of theinternational standards in the uniform labor legislation of Belarus, Kazakhstan and Russia.Keywords: harmonization, unification, European standards, principles of the labor law, right to work,international standards